Submarine Operational Risk Management Design in Support of the Indonesian Navy's Tasks - Saputro, H.D.; Suparno, Suparno; Astika, I Made Jiwa; Purnomo, Joko; Susilo, A.K. (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
This research discusses risk management faced by submarines and their crews. One of the risks that can occur is that the submarine cannot surface because the steering and propulsion system is not functioning properly. With the submarine unable to surface, it will cause the ship to sit on the seabed. A submarine that experiences an emergency so that it cannot surface is called a Distressed Submarine (DISSUB). Through the FMEA method the author identifies risks and aims to prioritize different causes based on their priority. FMEA itself is a systematic method, so it can find out the root of the problem that actually occurs. By knowing how urgent the priority is, the author can focus on problems that have a big impact on ship operational risks. It is hoped that the research results can be used as recommendations for mitigating risks that occur on submarines, providing a risk management framework for submarines.